TEORI PEMBELAJARAN DALAM PERSPEKTIF IBNU MISKAWAIH: ANALISIS TERHADAP PEMBINAAN AKHLAK DALAM PENDIDIKAN ISLAM - Nurul Safrina Jindan; Mutiara; Lina Marlina; Ali Maulida (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
This study discusses the concept of moral education according to Ibnu Miskawaih and its relevance in modern education. The aim of this research is to examine Ibnu Miskawaih’s thoughts on the nature of human beings, the concept of the soul, wisdom, the purpose of life, as well as learning theory and moral development in Islamic education. The method used is library research with a descriptive-analytical approach based on various literature related to Ibnu Miskawaih’s thoughts. The results of the study show that humans have three soul powers, namely desire (syahwat), anger (amarah), and rational, which must be balanced to form noble character. Morality is not innate, but can be formed through education, habituation, exemplary behavior, advice, and continuous moral training. Moral education aims to form individuals who are able to control their desires, use reason wisely, and achieve true happiness (as-sa’adah) in this world and the hereafter. Teachers and the environment play an important role in character formation through learning that is integrated with moral and spiritual values. Ibnu Miskawaih’s thoughts are also relevant to modern educational challenges, such as moral crisis, juvenile delinquency, low ethics, and the negative impact of technology. The concepts of habituation and exemplary behavior are in line with current character education. Thus, Ibnu Miskawaih’s thoughts provide an important contribution as a philosophical foundation in the development of character education that balances intellectual, moral, and spiritual aspects of students.